First report of birds infection by intestinal parasites in Khorramabad, west Iran - Badparva, Ebrahim (J Parasit Dis, 2014)
Parasitic infections in birds are omnipresent, even when they occur in low amounts, may result in subclinical diseases. There aren’t any studies, based on Iranian data, investigating the prevalence of intestinal parasitic infections in some birds’ species. We conducted a cross-sectional study between December 2011 and December 2012. The fecal samples were taken from 451 birds including hen, turkey, sparrow, pigeon and decorative birds. The samples screened for intestinal parasitic infections using direct smear, formalin–ether concentration technique, modified Ziehl–Neelsen staining, Culture in RPMI 1640 medium, sporulation with potassium dichromate and Trichrome and Giemsa staining. Out of 451 birds’ species, 157 (34.8 %), were infected with one or more type of intestinal parasites. We identified two nematode, two cestoda species and five protozoan parasites species. No trematodes were found in the samples studied. The parasites identified among birds involved Raillietina spp. (4.2 %) and Eimeria spp. (7.1 %) were the most common helminthes and protozoa respectively. From total of birds study, 12 (2.7 %) and 6 (1.3 %) have two and three mixed infections respectively. Intestinal parasitic infections are common in birds in west Iran. The future studies are needed in order to determine to which extent the infections influence mortality and performance of the birds.